2007
DOI: 10.1002/cne.21300
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain connectivity of the prefrontal cortex in the marmoset monkey (Callithrix jacchus): An anterograde and retrograde tract‐tracing study

Abstract: The cortical and subcortical forebrain connections of the marmoset prefrontal cortex (PFC) were examined by injecting the retrograde tracer, choleratoxin, and the anterograde tracer, biotin dextran amine, into four sites within the PFC. Two of the sites, the lateral and orbital regions, had previously been shown to provide functionally dissociable contributions to distinct forms of behavioral flexibility, attentional set-shifting and discrimination reversal learning, respectively. The dysgranular and agranular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
188
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(226 citation statements)
references
References 70 publications
26
188
1
1
Order By: Relevance
“…Lu et al (2012) demonstrated in rats that the default-mode network not only exists but also includes homologues of key structures noted in our work and that of others (Poppenk and Moscovitch, 2011) (eg, anterior cingulate cortex, retrosplenial cortex, and the dorsal hippocampus), which further strengthens the basis for parcellating hippocampus along its longitudinal axis. As such, converging evidence from noninvasive neuroimaging methods, along with those based on comparative anatomy techniques (ie, tract tracing) in rats (Van Groen and Wyss, 2003) and monkeys (Aggleton et al, 2012;Roberts et al, 2007), together provide support for the homology of hippocampal subdivisions that are the basis for this study (dorsal/ventral and posterior/anterior, respectively).…”
Section: A Default-mode Network-based Posterior Hippocampus Circuitrymentioning
confidence: 66%
“…Lu et al (2012) demonstrated in rats that the default-mode network not only exists but also includes homologues of key structures noted in our work and that of others (Poppenk and Moscovitch, 2011) (eg, anterior cingulate cortex, retrosplenial cortex, and the dorsal hippocampus), which further strengthens the basis for parcellating hippocampus along its longitudinal axis. As such, converging evidence from noninvasive neuroimaging methods, along with those based on comparative anatomy techniques (ie, tract tracing) in rats (Van Groen and Wyss, 2003) and monkeys (Aggleton et al, 2012;Roberts et al, 2007), together provide support for the homology of hippocampal subdivisions that are the basis for this study (dorsal/ventral and posterior/anterior, respectively).…”
Section: A Default-mode Network-based Posterior Hippocampus Circuitrymentioning
confidence: 66%
“…The vlPFC region targeted here (area 12, including 12l, 12m, and 12o) sends projections to both the mPFC and OFC (28,29), but the relative contribution of these projections is unknown. However, although mPFC manipulations have been shown to cause immediate alterations in cost-benefit decision making (6), inactivation of the OFC in the present study did not, making it unlikely that interactions between vlPFC and antOFC were contributing to performance.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia was monitored clinically and by pulse oximetry with capnography. Cannulae (Plastics One) were implanted into the vlPFC [double 6-mm-long cannulae, 1 mm apart, anteroposterior (AP) + 17.25/18.25, lateromedial (LM) adjusted in situ to give a depth greater than 3 mm at 8 0 ] or the antOFC (single 6-mm-long cannula, AP + 17, LM ± 3) having been adjusted where necessary in situ according to cortical depth (28). In the antOFC-cannulated animals, amygdala [single 14-mm-long cannula, AP + 9.3, LM ± 5.6, ventral (V) + 5] and anterior hippocampal (double 15-mm-long cannula, 1 mm apart, AP + 6, LM ± 5.75/7.75, V + 5) cannulae were added separately in an additional surgery.…”
Section: Methodsmentioning
confidence: 99%
“…First, to investigate the reward-nonspecific (or saliency-driven) perspective of mesolimbic function, we determine whether unpleasant pictures activate the NAc and mPFC to the same degree as pleasant pictures. We include mPFC in this examination because it is a dense cortical site of NAc interconnectivity (Ferry et al 2000;Roberts et al 2007) and is correlated with NAc activity in human reward studies (Knutson et al 2003;Rogers et al 2004). We also examine the sensitivity of NAc to pictures of equal valence, but varying emotional arousal, to explore whether the structure's graded responsivity to abstract reward predictors (Abler et al 2006;Knutson et al 2005;Preuschoff et al 2006) extends to inherently emotionevoking stimuli.…”
Section: Introductionmentioning
confidence: 99%